Does CEO risk-taking entrepreneurial spirit matter in firm cash holdings? - Meihua Zhou; Ruining Li; Jian Cao; Bin Lin (China Journal of Accounting Studies (CJAS), 2023)
The psychological factors of senior executives have an important impact on the firm's financial policies. In this paper, we investigate the association between CEO risk-taking entrepreneurial spirit and firm cash holdings, and find that firms with higher CEO risk-taking entrepreneurial spirit have less cash holdings. Further, we find that financing constraints can mitigate the negative association between CEO risk-taking entrepreneurial spirit and firm cash holdings, whereas financing needs enhances the association between them. Mechanism test illustrates that CEO risk-taking entrepreneurial spirit affects firm cash holdings through corporate investment. Finally, the results reveal that CEO risk-taking entrepreneurial spirit not only promotes the value of cash holdings, but also is significantly positively associated with both accounting performance and market performance. Our findings shed lights on the impact of executive psychological factors on financial decisions and have important implications for cash-holding decisions of listed firms.
Keywords: 650; CEO risk-taking; entrepreneurial spirit; financing constraints; financing needs; cash holdings